In silico analysis and functional validation of sinf-yc genes in foxtail millet setaria italica (l.) (Bangladesh Journal of Botany, 2024)
Nuclear transcription factor YCs (NF-YCs) are universally involved in plant development and abiotic stress response. As a typical C4 crop, foxtail millet has significant research value for studies of functional genes and mechanisms of plant stress resistance. To further investigate the correlation between the structure and function of the SiNF-YC genes in foxtail millet (Setaria italica), bioinformatic analysis of the SiNF-YCs on the subcellular localization, physicochemical properties, and cis acting elements were performed in this study. The results showed that a total of 12 SiNF-YC subfamily genes that distributed on chromosomes 1-9 were identified from the foxtail millet genome, which encoding 129-469 amino acids. The subcellular localization prediction results showed that the proteins encoded by this gene subfamily are mainly located in the nucleus, with a few being extracellular secreted. The multiple cis-elements related to drought resistance and light response are contained in the gene promoter region. Through haplotype analysis on the phenotypes of drought treated and heading dates that from five different regions, obvious haplotypes were identified except for SiNF-YC8 and SiNF-YC14. At last, drought regulation related gene SiNF-YC5 and heading date regulation related gene SiNF-YC10 were selected to explore superior gene haplotypes, laying a foundation for further exploring the functional genes involved in drought resistance and development within this gene family.Bangladesh j. Bot. 53(3): 535-543, 2024 (September)